Pengaruh spektrum cahaya dan giberelin terhadap perkecambahan kacang hijau (Vigna radiata L.) - Isbatullah, Muhammad; Sukmawaty, Eka; Masriany, Masriany; Meriem, Selis (Teknosains: Media Informasi Sains dan Teknologi, 2025)
Germination is an important initial process for seed-bearing plants. Several special treatments are carried out to break dormancy and stimulate seed germination. The aim of this study is to determine the effect of visible light spectrum and gibberellin hormone (GA3) on initiating the germination of mung beans. This research uses an experimental method with a completely randomized design (CRD) on mung bean plants (Vigna radiata L.). The results of the study showed that the single factor of red light influenced the growth of radicles and plumules of seedlings, while the single factor of GA3 at a concentration of 75 ppm affected the length of radicles. The combination of red light treatment and 75 ppm GA3 showed the best results for radicle elongation at the 12-hour observation time. The results obtained in this study can be used as a reference to improve the efficiency of mung bean germination.